2022
DOI: 10.1177/15248399221098015
|View full text |Cite
|
Sign up to set email alerts
|

Using Community-Based Participatory Research to Design a Patient and Practitioner-Centered Group Prenatal Care Model

Abstract: In response to disproportionately high rates of infant mortality and preterm birth among women of color and women in poverty in Fresno County, California, community and academic partners coordinated a community-based participatory research (CBPR) project with local residents. Social isolation and stress, inaccessible prenatal care, and dissatisfaction with care experiences were identified as leading predictors of poor birth outcomes. The PRECEDE-PROCEED framework was used to lead the CBPR effort that resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The original group prenatal care model had been developed through several community engagement activities; the adaptation process expanded on these activities by soliciting community feedback from additional stakeholders, including people with low income who had been pregnant during the pandemic. 23 We recruited from the Black Infant Health Program to increase the representation of Black/African American participants in the qualitative study. Participants in this qualitative study consisted of Medicaid-eligible individuals, who self-identified as Black, Latinx, or multi-racial, and were either pregnant or gave birth in Fresno, California, during the COVID-19 pandemic.…”
Section: Methodsmentioning
confidence: 99%
“…The original group prenatal care model had been developed through several community engagement activities; the adaptation process expanded on these activities by soliciting community feedback from additional stakeholders, including people with low income who had been pregnant during the pandemic. 23 We recruited from the Black Infant Health Program to increase the representation of Black/African American participants in the qualitative study. Participants in this qualitative study consisted of Medicaid-eligible individuals, who self-identified as Black, Latinx, or multi-racial, and were either pregnant or gave birth in Fresno, California, during the COVID-19 pandemic.…”
Section: Methodsmentioning
confidence: 99%